Between regulation and minority educational rights: secularism and the Indian Supreme Court - Bhatia, U (Routledge, 2019)
The Indian constitution is celebrated by several commentators for guarantees given to religious minorities in the sphere of education. These constitutional provisions have faced considerable criticism from Hindu nationalists in India, who see them as unfair concessions to minorities. At the same time, jurisprudence on minority educational rights has also been criticised for exempting schools from progressive legislation like the Right to Education (RTE) Act. Is it possible to provide an account of secularism that permits rights specifically for religious minorities, while, at the same time, allowing for these to be qualified in ways that do not undermine legislation like the RTE? In this article, it is argued that there is indeed a conception of secularism that responds to this dual challenge. Rajeev Bhargava’s notion of principled distance best captures the operation of secularism in the debate over minority educational rights in India. It is then demonstrated that this conception possesses the conceptual resources to defend rights for minority educational institutions while qualifying these insofar as other interests – such as those relating to the RTE – are concerned.